Integration of Financial Accounting and Digital Taxation in Indonesia - Wafa Virendra; Inka Mariska Zahra; Pani Aulia; Alya Fitri; Teuku Ardian Malulana (Penerbit Goodwood, 2025)
Purpose: This research aims to comprehensively analyze the challenges and opportunities involved in integrating financial accounting systems with digital taxation in Indonesia. This study focuses on structural barriers, institutional readiness, and the potential for enhancing efficiency and fiscal transparency through digitalization. Research methodology: The research was conducted using a descriptive qualitative approach with a literature study method. The sources of analysis were derived from scientific journals, government regulations, and previous studies related to the digitalization of accounting and taxation in Indonesia. Results: The findings indicate that the integration of digital systems still faces several obstacles, such as limited infrastructure, low digital literacy, suboptimal inter-agency coordination, and threats to data security. Nevertheless, digitalization also presents significant opportunities for improving tax administration efficiency, reporting accuracy, and data-driven monitoring through the utilization of big data, artificial intelligence, and e-reporting systems. Conclusions: Digital synergy between accounting and tax obligations is a strategic initiative to enhance the effectiveness and accountability of fiscal management. Its success requires regulatory harmonization, improved digital competence, and a robust data governance system. Limitations: This research is limited to the use of secondary data without the collection of primary data such as field research, interviews, or observations. Contribution: This research is limited to the use of secondary data without the collection of primary data such as field research, interviews, or observations.